Extortion: Criminal and Legal Analysis - Nurmukhammad Khamidov (International Journal of Law And Criminology, 2025)
The improvement of the quality of education increases the level of education of the future generation, the progress in the field of health care greatly contributes to the increase of the level of health of the population. The fact that the legislation, which is the basis for the development of these areas, is improving year by year is pleasing. To date, many of our laws have been either amended or radically updated. Because it is a priority to adapt these laws to the rapidly developing times. As a result of changes and improvements in this legislation, many crimes are prevented.